Enriquecimento de sementes de soja com níquel e molibdênio: produtividade, qualidade fisiológica e sanitária - Silva, Hellismar Wakson da (2020)
The production of high quality soy seeds is a challenge for the seed sector. Although little explored in the literature, it is known that plant mineral nutrition has a direct influence on seed production and quality, however, there is no consensus on the nutrients that relate to seed productivity and quality. Given the above, the objective of this study was to evaluate the effect of enriching soybean seeds with nickel and molybdenum on the physiological and health quality of the seeds produced. Two experiments were carried out, both with two soybean cultivars, where the seed treatment (nickel, cobalt and molybdenum) was combined with foliar applications of nickel and molybdenum. In both experiments, seed and protein productivity, chemical composition of seeds (oil, protein, nitrogen, nickel and molybdenum content), physiological quality (first count, germination, accelerated aging, electrical conductivity, emergence and speed index) were evaluated emergency) and sanitary quality (incidence of Aspergillus spp., C. kikuchii, Fusarium spp.). The treatment of soybean seeds with nickel, cobalt and molybdenum associated with the application of 10 g ha-1 of nickel increases the leaf contents of phosphorus, potassium, calcium, sulfur and boron. For the cultivar SYN 13610, seed treatment followed by foliar applications associated or not with 10 g ha-1 of nickel and 40 g ha-1 of molybdenum result in higher productivity. The application of molybdenum via seed treatment increases the content of this micronutrient in the seeds produced, an increase optimized with 40 g ha-1 of molybdenum via leaf. The foliar content of molybdenum increases with the treatment of seeds containing Ni, Co and Mo, but reduces with foliar application of nickel in TMG 7062. Isolated or associated applications of nickel in the V6 stage and molybdenum in R5.1 increase seed productivity of TMG 7062 and the total carbohydrate content in the seeds of M 6410. For the cultivar TMG 7062 the treatment of seeds with Ni, Co and Mo increases the retention of seeds in the 7.0 mm sieve. Both studied cultivars respond in a similar way to the enrichment of seeds with molybdenum, whose highest levels are obtained with the application of Ni, Co and Mo in the treatment of seeds followed by the foliar application of 40 g of Mo ha-1 at the R5.1 stage, associated or not with the application of 10 g of Ni ha-1 in the V6 stage. The enrichment of seeds with nickel improves the physiological quality, but increases the incidence of Aspergillus and Fusarium sp. On the other hand, enrichment of seeds with molybdenum has a high relationship with the protein and nitrogen content in the seeds, which do not contribute with quality of soybean seeds.